1994
DOI: 10.1055/s-2007-997188
|View full text |Cite
|
Sign up to set email alerts
|

Die Arteria lusoria - seltene Ursache einer Dysphagie

Abstract: A rare case of a 29-year old woman with aberrant right subclavian artery (A. lusoria) causing dysphagia is presented. This abnormality is generally silent and often an incidental x-ray finding. By means of a median thoracotomy the anomalous vessel was divided at its point of origin and an anastomosis to the ascending aorta with a graft was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…

lization shows good long-term results [1]. Recent reports showed that on-pump beating heart valve replacement is effective even in the presence of aortic dissections [4,5]. Aortic root replacement with the Cabrol procedure can be performed with a good surgical exposure and ease of maneuver on the beating heart.

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…

lization shows good long-term results [1]. Recent reports showed that on-pump beating heart valve replacement is effective even in the presence of aortic dissections [4,5]. Aortic root replacement with the Cabrol procedure can be performed with a good surgical exposure and ease of maneuver on the beating heart.

…”
mentioning
confidence: 99%
“…Aortic root replacement with the Cabrol procedure can be performed with a good surgical exposure and ease of maneuver on the beating heart. This method has its advantages, especially for high-risk patients, such as those with compromised left ventricle function and renal failure [4,5,10]. Despite the advantages of this technique, it has several disadvantages, such as the exact sizing of the graft length, kinking, right coronary ostial occlusion and reduced long-term patency due to the artificial grafts.…”
mentioning
confidence: 99%